Student's epistemological beliefs and motivation across disciplines - Miravite, Lonalee M. (2009)
This study explored students' beliefs about knowledge and knowing in the different disciplinary contexts to obtain baseline data on student epistemologies based on Biglan's classification of academic domains. A survey was administered to students of different educational disciplines to determine their epistemological beliefs and motivation. Focus group discussions were used to substantiate findings. Results showed that sutdents in all disciplines held more sophisticated views in the structure, stability, and justification of knowledge. However, they have naive views on the sources of knowledge. Mastery-goal orientation was proven to be related to sophisticated beliefs about the structure and justification of knowledge while performance-goal orientation was related to sophisticated beliefs about the stability of knowledge.